Representación de lo femenino en la novela “La Emancipada” del escritor ecuatoriano Miguel Riofrío. - Garces Vizuete, Lizzeth Carolina (2023)
The research's objective is to analyze the representation of the feminine in the character of Rosaura as the protagonist of the novel La Emancipada by the Ecuadorian writer Miguel Riofrío in the context of the nineteenth century. Through the nature of Rosaura, the novel's protagonist, the roles and stereotypes imposed on women of the time are revealed. Rosaura is presented as a woman subjected to social and family norms whose primary purpose is to fulfill her role as a wife and mother. However, as the plot progresses, Rosaura defies these limitations and seeks her emancipation, showing the struggle and resistance of women in a patriarchal context. The novel exposes the tension between traditional feminine characteristics and the liberal tendencies of modernity. While Rosaura embodies the female roles and stereotypes of the time, she also seeks her autonomy and challenges the established norms. The present research had a qualitative, descriptive approach and bibliographic-documentary design and used the novel's theoretical basis of hermeneutic content analysis. The analysis of La Emancipada allows us to understand the complexity of the feminine representation in the story and its relevance in the historical and social context. In addition, it invites us to reflect on the significance of these issues today and the importance of questioning gender stereotypes to achieve a more egalitarian and just society.